Advances in the economic analysis of participatory and labor-managed firms. Vol. 12 - DeVaro, Jed. (Bingley, U.K. : Emerald, 2011)
This 12th edition of Advances in the Economic Analysis of Participatory and Labor-Managed Firms contains a stimulating collection of original papers spanning a wide variety of topics. Part 1 of the volume contains three papers on the subject of job design and organizational performance, covering the determinants of multiskilling from a theoretical perspective and also the empirical effect of multiskilling and teams on financial performance. Part 2 of the volume concerns compensation, worker attitudes, and productivity. Papers in this section cover the effect of rules and costs on employer-provided health insurance, majority ownership and executive compensation, worker attitudes towards different forms of employee ownership and variable pay, and an analysis of performance-related pay, unions, and productivity in Italy. Part 3 contains three studies of worker cooperatives and nonprofit organizations in Italy, Spain, and Uruguay. The volume concludes with a debate on free trade and the ecological effects of alternative socio-economic systems.
Specialization, multiskilling, and allocation of decision rights / Hideo Owan -- The effect of multiskilling on labor productivity, product quality, and financial performance / Martin Farnham, Emma Hutchinson -- Teams, autonomy, and the financial performance of firms : new evidence from panel data / Jed DeVaro -- How do rules and costs affect a firm's setting of benefits? : the case of health insurance and workforce skills / Nan L. Maxwell -- Majority ownership and chief executive compensation / Derek C. Jones, Niels Mygind -- Worker attitudes toward employee ownership, profit sharing and variable pay / Fidan Ana Kurtulus, Douglas Kruse, Joseph Blasi -- Performance-related pay, unions, and productivity in Italy : evidence from quantile regressions / Mirella Damiani, Andrea Ricci -- Profit reinvestment in Italian worker cooperatives as a contribution to a common good : an empirical analysis on workers' perception and motivation / Cecilia Navarra -- Does training policy help to attract, retain, and develop valuable human resources? : analysis from the Mondragon case / Imanol Basterretxea, Eneka Albizu -- Governance and behavior in nonprofits : analysis of Uruguayan health care organizations / Juan Jose Barrios, Mieke Meurs -- Capitalism, economic democracy, and ecological destruction of our planet / Jaroslav Vanek -- The case for capitalism : a comment on Jaroslav Vanek's'Capitalism, economic democracy, and ecological destruction of our planet' / Jed DeVaro, Adrian Stoian -- Rejoinder / Jaroslav Vanek.
Keywords: Management -- Employee participation